2015
DOI: 10.5125/jkaoms.2015.41.3.156
|View full text |Cite
|
Sign up to set email alerts
|

Stability of unilateral sagittal split ramus osteotomy for correction of facial asymmetry: long-term case series and literature review

Abstract: Bilateral sagittal split ramus osteotomy is considered a standard technique in mandibular orthognathic surgeries to reduce unexpected bilateral stress in the temporomandibular joints. Unilateral sagittal split ramus osteotomy (USSO) was recently introduced to correct facial asymmetry caused by asymmetric mandibular prognathism and has shown favorable outcomes. If unilateral surgery could guarantee long-term postoperative stability as well as favorable results, operation time and the incidence of postoperative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…In reports of patients treated with USSO, the patients did not exhibit TMJ dysfunction, pain, limited mouth opening following surgery, or evidence of condylar resorption [30,31]. In the present study, similar results were found but the reported symptoms were not quantified for level of severity.…”
Section: Discussionsupporting
confidence: 83%
“…In reports of patients treated with USSO, the patients did not exhibit TMJ dysfunction, pain, limited mouth opening following surgery, or evidence of condylar resorption [30,31]. In the present study, similar results were found but the reported symptoms were not quantified for level of severity.…”
Section: Discussionsupporting
confidence: 83%
“…SSO is a well-established procedure in the field of maxillofacial surgery. Although its main use lies in the orthognathic field, it can be a great tool in selected trauma cases [8][9][10][11][12]. For this procedure, the placement of dental implants to restore dentition is unnecessary because of the new preplanned occlusion employing existing teeth.…”
Section: Discussionmentioning
confidence: 99%
“…It is applicable in mandibular advancements, setbacks, ramus elongation, and all types of angular movements. However, it can be a great tool in the secondary treatment of the mandible fractures, e.g., the treatment of malocclusion resulting from condylar fractures with the shortening of the mandibular ramus [8,9] and reconstruction procedures of the mandible [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…It is necessary to clarify to what extent mandibular deviation can be corrected by USSRO with stable postoperative outcomes. In the study by Lee, S., et al, 7-mm unilateral mandibular movement after USSO would rotate the mandibular condyle 3° to 4° in nonosteotomy side without influencing TMJ function [27]. However, Beukes, J., et al suggested that USSRO should only be performed for small mandibular asymmetries of less than 5 mm [2].…”
Section: Discussionmentioning
confidence: 99%